‘Some Days Are Not a Good Day to Be a Mum’: Exploring Lived Experiences of Guilt and Shame in the Early Postpartum Period - Leanne Jackson; Emily O’Donoghue; Jasmin Helm; Rita Gentilcore; Anisha Hussain (European Journal of Investigation in Health, Psychology and Education)
The first 16 weeks postpartum are particularly challenging for a new mother and are associated with an elevated risk of experiencing psychological distress. Guilt and shame have been identified as significant predictors of other forms of psychological distress, such as anxiety and depression. However, guilt and shame are poorly distinguished in pre-existing literature. The current study used inductive thematic analysis to explore lived experiences of guilt and shame in the early postpartum period. Semi-structured interviews were conducted with 20 women who had given birth in the past 16 weeks and who were residing in the UK at the time of the investigation. All those interviewed had internalised unrealistic mothering ideals. Physical constraints on one’s parenting abilities, due to birth recovery, exacerbated postpartum guilt and shame. Other sources of guilt and shame included body dissatisfaction and making comparisons against other mothers and media depictions of motherhood. Participants were hesitant to confide in others about parenting challenges due to fears of judgement, which perpetuated the shame-concealment cycle. Future research should prioritise the development of interventions designed to target a harsh parenting inner critic, and the re-framing of cognitive biases, to nurture more realistic and self-compassionate beliefs about motherhood. For practice, current findings mirror previous calls for intimate partners to be actively included in routine appointments, to provide healthcare practitioners with specialist training in postpartum mental health, and to educate mothers on responsible social media use.